Avaliação das características físicas e metalúrgicas de um briquete de pó de aciaria e o impactto ambiental de seu uso como refrigerante no convertedor LD - Mariana Alves Ribeiro (2023)
Briquetting is a cold agglomeration technique applied to different materials, especially in steelmaking, to agglomerate iron ore and other fines. This practice contributes to the circular economy by reusing by-products generated in steelmaking processes as raw materials. Currently, studies are exploring the use of briquettes as an alternative to pellets and sinter in steel production due to the lower complexity and energy consumption in their manufacture, resulting in lower carbon emissions throughout the value chain. The feasibility of using briquettes in steelmaking processes depends on its performance considering specific parameters, these parameters can be different depending on the application of the agglomerates. Therefore, in this study, steelmaking powder and sludge briquettes were evaluated in relation to moisture and water absorption and also in relation to their mechanical resistance. These results were compared with the performance of pellets and sinter, in which the briquettes present favorable results for their use, but are different from other agglomerates, whether due to porosity or chemical composition. The lack of a high-temperature process in briquettes production can also be associated with the results. The briquettes were also submitted to thermogravimetric analysis and high temperature tests, in addition to thermodynamic analysis to evaluate their cooling capacity in LD converters. The briquette’s cooling power was significantly higher than that of the pellets and sinter, commonly used for this function. The chemical composition of the briquette favors the slag formation, avoiding problems of solidification and loss of fluidity. The study also addresses the loss of mass and possible degradation of the briquette in conditions close to the ones observed in steelmaking. Furthermore, the environmental impact of replacing pellets and sinter with briquettes in steel production was evaluated, considering carbon emissions in scopes 1 and 3. The analysis indicated that replacing sinter has a higher impact in Scope 1, while replacing of pellets has the higher impact on Scope 3. These results highlight the relevance of the circular economy and the reduction of greenhouse gas emissions in the steel industry, highlighting the potential of waste briquettes for use as coolants considering the metallurgical properties and also the environmental impact.